Industrial ecologyapplied to the furniture industry - Kravchenko, Grégory Adad; Pasqualetto, Antônio; Ferreira, Evaldo de Melo (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The furniture industries use as raw inputs that come from renewable resources such as wood, natural fibers, leather and non-renewable materials such as metals, glass and polymers. All are directly related to the generation of post-production waste by industries, may cause contamination of soil, water or air pollutant generating sources. Using as premises the environmental concepts of eco-efficiency, Ecodesign and Environmental Management System, the literature review with the aim of knowing the strategies and tools relevant to industrial processes was performed by subsidizing conducting quantitative research with the productive sector furniture of the State of Goiás.